2012
DOI: 10.1186/1754-6834-5-22
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic evaluation of 2nd generation bioethanol production from sugar cane bagasse and leaves integrated with the sugar-based ethanol process

Abstract: BackgroundBioethanol produced from the lignocellulosic fractions of sugar cane (bagasse and leaves), i.e. second generation (2G) bioethanol, has a promising market potential as an automotive fuel; however, the process is still under investigation on pilot/demonstration scale. From a process perspective, improvements in plant design can lower the production cost, providing better profitability and competitiveness if the conversion of the whole sugar cane is considered. Simulations have been performed with Aspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
176
1
29

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(211 citation statements)
references
References 25 publications
5
176
1
29
Order By: Relevance
“…Its sugar has been used for firstgeneration biofuels in the last 10 to 20 years, while its lignocellulosic biomass has only recently been exploited for second-generation biofuels. Sugarcane lignocellulosic biomass is derived mostly from its millable stalk and partially from leaves and green tops, estimated to be two thirds of the total sugarcane biomass produced [39][40][41]. Hence, developing sugarcane varieties with a desirable fiber/sugar ratio within this biomass fraction, from the current diverse germplasm collections, is essential and should be advanced in parallel a b c d…”
Section: Discussionmentioning
confidence: 99%
“…Its sugar has been used for firstgeneration biofuels in the last 10 to 20 years, while its lignocellulosic biomass has only recently been exploited for second-generation biofuels. Sugarcane lignocellulosic biomass is derived mostly from its millable stalk and partially from leaves and green tops, estimated to be two thirds of the total sugarcane biomass produced [39][40][41]. Hence, developing sugarcane varieties with a desirable fiber/sugar ratio within this biomass fraction, from the current diverse germplasm collections, is essential and should be advanced in parallel a b c d…”
Section: Discussionmentioning
confidence: 99%
“…However, in some articles, second-generation ethanol from lignocellulosic residues is investigated from this point of view (Macrelli et al 2012). For instance, by targeting the ethanol production of 45 l per dry ton of sugarcane and estimating the costs as follows: enzymes (0.341 US $/l), acid (0.08 US $/l), base (0.02 US $/l), water consumption (0.045 US $/l), vinasse sales (-0.003 US $/l), labor, maintenance, and insurance (0.148 US $/l), electricity (0.357 US $/l), and capital cost (0.56 US $/l), the minimum ethanol selling price would be calculated as 1.548 US $/l (Macrelli et al 2012). Although this estimation contains the cost of pretreatments in which either of chemicals or energy is required, the price of other nutrients such as yeast extract and synthetic salts which can increase the costs substantially is not included.…”
Section: Economic Perspectivementioning
confidence: 99%
“…This study identified the Midwest and South as the regions of the country with the greatest potential for feedstock crop production, with emphasis on sweet sorghum and energy cane. Macrelli et al evaluated the technical and economic prospects of bioethanol produced from the lignocellulosic portions of sugar cane (bagasse and leaves) associated with the production of sugar cane bioethanol on Brazil [6]. Utilizing simulation analysis, results indicated that production of second generation bioethanol from sugar cane bagasse and leaves in Brazil was currently economically competitive starch-based bioethanol production in Europe and, further, that sugar cane bioethanol could be produced at a lower cost with enzyme costs continuing to decline and if subsidies were used to compensate for the opportunity cost from the sale of excess electricity.…”
Section: Review Of Relevant Previous Researchmentioning
confidence: 99%